‘Abominable crime': examining the constitutionality of the Jamaican sodomy law through the lens of the general savings law clause - Wheatle, S; Seshauna Wheatle (2011)
In jurisdictions where the criminalization of sodomy has been invalidated by judicial order, this has generally been achieved through a determination that an identified right is infringed and that there is justification for that infringement. However, in Jamaica, a modified approach is required owing to the existence of the General Savings Law Clause (GSLC), which shields laws existing before the entry into force of the Constitution of Jamaica from invalidity with the fundamental rights provisions in the Constitution. The sodomy law is one such existing law. Accordingly, it is advisable to begin the analytical process with the general savings law clause. Therefore, my thesis presents two arguments for obviating the clause. The first is an argument that the sodomy law is inconsistent with the constitutional principle of rule of law (as opposed to a provision). Accordingly, the GSLC does not apply here because the clause only saves laws inconsistent with constitutional provisions but does not speak to constitutional principles. The thesis then presents a case for a substantive conception of the rule of law and discusses whether the rule of law includes a conception of equality which requires invalidation of prohibitions of consensual anal intercourse between consenting adults. The second argument is that a reinterpretation of the GSLC could enable a successful challenge to the criminalization of sodomy by permitting the court to modify the law that criminalizes it. This argument relies on the use of a clause in the Constitution (Order in Council) that mandates the modification of existing laws in particular circumstances. I propose that, by this method of modification, the court could decriminalize anal intercourse between consenting adults.